INTEGRASI PEMBELAJARAN BAHASA INGGRIS GUNA MENINGKATKAN KUALITAS PELAYANAN DALAM SEKTOR INDUSTRI PERHOTELAN - Silalahi, Ronald Maraden Parlindungan; Murniati, Murniati; Widianingtyas, Nugraheni (Universitas Bunda Mulia, 2023)
English for Specific Purposes (ESP) in the hospitality industry context answers problems related to service quality in the hospitality industry. It is experienced by IBIS Style Hotel – Gajah Mada as part (branch) of the largest hotel franchise chain in Indonesia. IBIS Style Hotel – Gajah Mada feels that the work team must improve their English skills, especially when carrying out daily tasks and routines. It underlies the implementation of Community Services (ABDIMAS), which involves Bunda Mulia University as the executor and IBIS Style as a partner. Realizing these problems, programmed (incidental) ABDIMAS activities were carried out, which were described in three stages. First, the initiation or understanding of problems and constraints faced by partners. Second, the execution or implementation of activities carried out to answer Partner problems which in this case is carried out through enrichment programs in 4 major themes developed in 12 meetings. Third, the implementation that focuses on the dissemination of academic work produced as a manifestation of the principle of transparency. Activities are measured quantitatively with four measurement components (educational, objective, accountable, and transparent). Analysis of the four measuring components shows that implementing programmed (incidental) activities is carried out well regarding impact, form, and benefits for all participants.